Socioeconomic Status, Parental Involvement and Implications for Subjective Well-Being During the Global Pandemic of Covid-19 - Treviño, Ernesto; Miranda, Catalina; Hernández, Macarena; Villalobos, Cristóbal (Frontiers in Education, 2021)
School closures prompted by the global outbreak of COVID-19 have impacted children's subjective well-being. In this context, a growing number of studies has pointed out that the experience of learning at home is an essential factor influencing their subjective well-being, raising the importance of parental involvement in the educational process of their children. This article explores the formal and informal parental practices of home learning during school closures period in 19 countries and their explanatory factors, with the further aim of discussing their implications for children's subjective well-being. The study uses the International COVID-19 Impact on Parental Engagement Study (ICIPES) database and develops a regression analysis of family, child, and school factors predicting parental involvement in homeschooling. The main findings show that parents' socioeconomic status (SES) is a critical predictor of both formal and informal parental practices. In addition, the results denote the impact of other factors, such as the level of parental confidence with the use of technology and children's age and gender (in the case of informal activities). Based on these findings, the article discusses policy implications to promote parental involvement and children's subjective well-being.